THE POSSIBILITIES OF THE STRUCTURE AND VARIABILITY EVALUATION OF INVENTORY CONSUMPTION - Petr Besta; Kamila Janovská; Monika Bumbová (Acta Logistica, 2015)
Inventory can be evaluated from the point of view of a number of aspects. Production and trade organizations nowadays are under great pressure from their competitors and face high expectations from their customers. That is why the cost cutting in all areas can provide a significant competitive advantage. Inventory and its management and administration can therefore represent a source of substantial potential savings. Large inventory volume can significantly increase the costs, but its shortage influences the course of the manufacturing process and, ultimately, the customer satisfaction. It is therefore necessary to continuously optimize the inventory management system in the enterprise. The conducted research also involved an analysis of the structure and variability of the inventory consumption in a business organization dealing with the sale and storage of metallurgical materials. The objective of this article is to evaluate the possibility of the application of the tools used to analyze the structure and variability of inventories in the industrial and commercial practice.